“Efecto de la aplicación de fertilizantes foliares en fase reproductiva, sobre el rendimiento de dos variedades de café (Coffea arábica L.), en la finca Agro Loja, parroquia Malacatos” - Cartuche Jaura, Carolina Fernanda (2024)
Ecuadorian coffee is one of the most popular products at the international level, recognized for its quality. However, little research has been done on the effect of foliar nutrition during the flowering and fruit set stages. For this reason, it is necessary to provide information on fertilization programs in the reproductive stage, seeking to optimize the productive capacity. The objective of the present study was to determine the effect of foliar fertilization applied during the reproductive stage on the yield of two coffee varieties at the Agro Loja farm in Malacatos. For this purpose, a field trial was carried out under an experimental design of divided fields, taking the typica and caturra varieties as the main plot, and the subplots had three different treatments using foliar fertilizers, Poliquel calcium, Agasol 10- 5-40, their combination, plus the control. The treatments were applied every 20 days from floral pre- anthesis until about 181 days after pre-anthesis, for a total of 10 applications. The following variables were evaluated: fruit set, fruit growth, phenology, fruit abscission, °brix, pH, titratable acidity, cherry epicarp colorimetry, production per plant and hectare. In the results, no significant differences were found between the interaction of variety and fertilization in the variables of fruit set, abscission, titratable acidity and colorimetry of the epicarp, except for °brix which presented significant differences independently between the two factors with respect to the var. typica obtained 20.43 °brix and fertilization with Poliquel calcium obtained 20.78 °brix. Likewise, the factor fertilization with Poliquel + Agasol 10- 5-40 significantly favored the polar diameter. In addition, it was observed that the variety factor had a significant influence on equatorial diameter, pH, number of flowers and production, reaching 1.90 kg plant and 6284 kg per hectare with respect to typica.